Bovine Herpesvirus Major Glycoproteins: I. Antigenic Differences Of bG, gC, And gD Between BHV-1 And BHV-5 II. Molecuiar Cloning And Sequencing Of BHV-5 gD Gene III. Fine Mapping Of Linear Neutralizing Epitopes On BHV-1 gD - Abdelmagid, Omar Yousif (Kansas State University, 1994)
The BHV-5 glycoprptein D (gD) gene was cloned, sequenced and used as variant sequence to identify two highly neutralizing epitopes on the BHV-1 gD. The BHV-1-specific monoclonal antibodies (MAbs) 3402 and R54 were tested against overlapping TrpE-gD fusion proteins expressed from a series of BHV-1 gD ORF subfragments. The reactivity of the MAbs with the expressed fragments on western blots located the epitopes between amino acid 52-115 and amino acid 165-216 for 3402 and R54 MAb respectively. The precise amino acid sequences specifying the epitopes were identified on the two fragments by amino acid sequence analysis and comparison with the corresponding regions of the variant BHV-5 gD sequences. A few amino acid changes occurred in these regions of BHV-5 gD have resulted in loss of MAb reactivity with the BHV-5 gD on western blots. Based on antigenic analysis of these regions, peptides covering amino acid 92-106 (3402 epitope) and 202-213 (R54 epitope) were synthesized and examined for their epitope activity. Each peptide reduced the neutralizing ability of the corresponding MAb in a dosedependant manner. Antisera produced in rabbits to KLH-conjugated peptides recognized the parent gD on western blot, but had low neutralizing antibody titers against BHV-1. Bovine convalescent sera with high neutralizing antibody titers against BHV-1 reacted with bacterially-expressed protein containing both of the epitopes suggesting that these neutralizing linear epitopes are important in inducing immunity to BHV-1 during natural infections. The BHV-5 (TX89 strain) gD encoding gene was mapped to BamHI-C genomic fragment between map units 0.887-0.897. The gene encodes a predicted protein of 417 amino acids with characteristics typical of a glycoprotein. Comparison of the BHV-5 gD and BHV-1 gD predicted amino acid sequences revealed significant homology in the amino-terminal two-third of the molecule. All seven cysteine residues characteristic of alphaherpesvirus gD homologues are identically aligned between the two gD molecules. The carboxy-terminal one-third is highly variable and contains several significant insertion and deletions. These differences may be important in the ditferential pathogenesis of respiratory disease and neurological disease by BHV-1 and BHV-5 respectively.